DIABETES SELF MANAGEMENT EDUCATION AGAINST TYPE 2 DM PATIENTS INDEPENDENCE IN MANAGING DIET - Hariyono Hariyono; Okaria Nur Sababa (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. Diabetes mellitus has been the cause of 4.6 million deaths. In addition, health expenditure for diabetes mellitus has reached 465 billion USD. Complications experienced by patients with type 2 diabetes mellitus that causes the sufferer to experience dependence in regulating dietary patterns. Patients depend in managing the diet due to a lack of knowledge and lack of motivation in self-care. The purpose of this study was to identify the effectiveness of Diabetes Self-Management Education to independence yipe 2 diabetic patients in managing the diet. Method. This research was aPre-experimental study. Research design was one group pre-post-test design. The sampling technique used simple random sampling with 30 samples. Data was analyze by using Wilcoxon Signed Rank Test with a significance value of α = 0.05. Result. Pre-test results showed that almost all respondents (80%) or 24 samples in the category of partial care. The post-test results showed that the majority (56.7%) or 17 respondents in the category of minimal care. Statistical analysis showed Wilcoxon p = 0.000. Discussion. The conclusion of this research showed that the effects of Diabetes Self-Management Education on patient autonomy in managing diet in type 2 diabetes patient. Keywords: Diabetes Self-Management Education, Diet, Independence